Exposure - Askew, Kim (Askew, Kim. Twisted lit novel., 2012)
Skye Kingston is a shy shutterbug who prefers observing life from behind her camera lens. She doesn't know she's stunning, and comes off the sidelines only when she's forced to by the terrifying events of one treacherous school year in Alaska. A boy named Duncan is dead, and his death may or may not be an accident. Skye's three new best friends are eerily able to foretell the future, and cheerleader Beth might be more than a social climber--she quite probably is a sociopath. Then there's Skye's growing attraction to the school hottie, Craig, As Skye falls for Craig, she also slowly realizes that he is caught in the crosshairs of a deadly plot. Can she save Craig and herself from a murderous fate?